Saving the trees. [article].
The European Commission asked the European Court of Justice (ECJ) to fine Poland for ignoring an earlier order to halt logging in parts of the forest protected under EU law - in effect, nearly all of the 60,000 hectares of it that lie in Poland. It pits competing visions of environmental stewardship and economic development, and of Poland's path under the right-wing Law and Justice (PIS) party.
Keywords: Trees - Periodicals; Over logging - Europe - Periodicals; Ancient forest - Europe - Periodicals